2004
DOI: 10.1182/blood-2003-12-4165
|View full text |Cite
|
Sign up to set email alerts
|

Epitope mapping of ADAMTS13 autoantibodies in acquired thrombotic thrombocytopenic purpura

Abstract: Severe deficiency of the von Willebrand factor (VWF)-cleaving protease ADAMTS13 can lead to thrombotic thrombocytopenic purpura (TTP), a disease associated with the widespread formation of platelet-rich thrombi in many organs. Autoantibodies that inactivate ADAMTS13 are the most frequent cause of acquired TTP. Little is known about epitope specificity and reactivity of anti-ADAMTS13 antibodies. In this study, a series of ADAMTS13 domains were expressed in Escherichia coli, and the reactivity of purified recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
171
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(192 citation statements)
references
References 46 publications
14
171
1
6
Order By: Relevance
“…The main antigenic epitope recognized by these anti-ADAMTS13 autoantibodies was found to reside in the ADAMTS13 spacer domain (Figure 2B), which has been reported to contain the primary antigenic epitope of inhibitory anti-ADAMTS13 antibodies. 19,[21][22][23] This suggests a pathophysiological role of the anti-ADAMTS13 autoantibodies present in low titers during the first acute episode despite normal in vitro ADAMTS13 activity documented by three different assays.…”
Section: Discussionmentioning
confidence: 91%
“…The main antigenic epitope recognized by these anti-ADAMTS13 autoantibodies was found to reside in the ADAMTS13 spacer domain (Figure 2B), which has been reported to contain the primary antigenic epitope of inhibitory anti-ADAMTS13 antibodies. 19,[21][22][23] This suggests a pathophysiological role of the anti-ADAMTS13 autoantibodies present in low titers during the first acute episode despite normal in vitro ADAMTS13 activity documented by three different assays.…”
Section: Discussionmentioning
confidence: 91%
“…23,24 Moreover, certain strains of mice have been identified that express an ADAMTS13 variant that lacks the CUB domains (and also TSP1-7 and TSP1-8), 27 further suggesting that the functions of these domains are not critical in vivo. Although autoantibodies against the CUB domains have been found in patients with acquired TTP, 28 it is unclear whether these compromise ADAMTS13 function. The recent study reporting that CUB domain-derived peptides inhibit VWF-cleaving activity under flowing, but not static, conditions might, however, imply a potentially important functional role to these domains.…”
Section: Discussionmentioning
confidence: 99%
“…The spacer domain is required for binding to a short fragment in the VWF A2 domain downstream of the cleavage site [24] and also for recognition by TTP IgG [21;25]. One study also detected interaction of TTP IgG with other domain fragments [26], although this observation remains controversial. The TSR 2-8 region is required for effective cleavage of VWF multimers but not of the VWF A2 fragment.…”
Section: Adamts13 -Structure and Functionmentioning
confidence: 99%